Making a Bible Enterprise: James Thomson and the British and Foreign Bible Society in British North America, 1838–1842 - Barnard, Stuart (Mémoires du livre / Studies in Book Culture)

(untitled) (Groupe de recherches et d’études sur le livre au Québec, 2015)
The reading and study of bibles in Canada has shaped the ways in which the Christian faith is practiced, but it was not until the middle of the nineteenth century that bibles became widely available. This article examines the historical developments of bible distribution in British North America, focusing on the British and Foreign Bible Society (BFBS), which became the largest distributor of bibles in the world. Strengthening the BFBS's Canadian influence was its agent James Thomson, whose work in British North America between 1838 and 1842 expanded the organization’s reach and ensured an ample supply of bibles in the colonies. Through the expansion of local Bible Society auxiliaries and the establishment of distribution networks, Thomson laid the foundations for the BFBS’s success in establishing a successful bible enterprise that would dominate the trade in British North America for the rest of the century.